Wiener – Hopf technique for economical study - Rogosin, Sergei V.; Dubatovskaya, Marina V. (Journal of the Belarusian State University. Economics, 2024)
Wiener – Hopf factorisation of complex functions is used in probability theory, ﬁnancial mathematics, insurance, queueing theory, acoustic, radio-engineering, ﬂuid and gas mechanics, fracture mechanics, etc. Some of these applications of mathematics are described in original research papers and surveys. This article presents a survey of the results devoted to the application of the Wiener – Hopf method in the economic investigations.